2021
DOI: 10.3390/antiox11010047
|View full text |Cite
|
Sign up to set email alerts
|

The Epidermis: Redox Governor of Health and Diseases

Abstract: A functional epithelial barrier necessitates protection against dehydration, and ichthyoses are caused by defects in maintaining the permeability barrier in the stratum corneum (SC), the uppermost protective layer composed of dead cells and secretory materials from the living layer stratum granulosum (SG). We have found that loricrin (LOR) is an essential effector of cornification that occurs in the uppermost layer of SG (SG1). LOR promotes the maturation of corneocytes and extracellular adhesion structure thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 192 publications
(292 reference statements)
0
7
0
Order By: Relevance
“…Nrf2 is also a key regulator of the epidermal barrier, which activates a "rescue" pathway in LOR-deficient mice. The combined loss of LOR and Nrf2 signaling in keratinocytes caused perinatal death of mice because of an impaired epidermal barrier and consequent desiccation (Huebner et al, 2012, Ishitsuka andRoop, 2021). However, overactivation of NRF2 in keratinocytes of transgenic mice also resulted in a defective barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is also a key regulator of the epidermal barrier, which activates a "rescue" pathway in LOR-deficient mice. The combined loss of LOR and Nrf2 signaling in keratinocytes caused perinatal death of mice because of an impaired epidermal barrier and consequent desiccation (Huebner et al, 2012, Ishitsuka andRoop, 2021). However, overactivation of NRF2 in keratinocytes of transgenic mice also resulted in a defective barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The late phase of keratinocyte differentiation involves a complete remodeling of the cell including the breakdown of mitochondria and other organelles [ 6 , 44 , 45 ]. It is conceivable that these processes affect the redox balance which is important for proper cornification [ 46 ]. The results of the present study suggest that HO-1 is either not involved in controlling oxidative stress during cornification or its function is redundant due to the presence of other anti-oxidant protection mechanisms such as HO-2 [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that these processes affect the redox balance which is important for proper cornification [ 46 ]. The results of the present study suggest that HO-1 is either not involved in controlling oxidative stress during cornification or its function is redundant due to the presence of other anti-oxidant protection mechanisms such as HO-2 [ 46 , 47 ]. Importantly, epidermal HO-1 may have a critical function when the skin is exposed to high levels of oxidative stress [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 also protected the skin against the chemical carcinogen 7,12-dimethylbenz(a)anthracene (DMBA) [ 39 , 40 ]. Furthermore, we have recently found that LOR and the KEAP1-NRF2 system coordinately upregulate robust antioxidative responses and exert xenobiotic metabolism in the epidermis [ 4 , 5 , 41 ]. In the absence of LOR, NRF2 directly upregulated thiol-rich CE proteins, small proline-rich protein 2 (SPRR2) [ 42 ], and late cornified envelope proteins [ 43 ], thereby compensating for the disrupted thiol gradient and epidermal barrier functions.…”
Section: Nrf2 As a Regulator Of Keratinizationmentioning
confidence: 99%
“…A previous study showed that Keap1 -knockout mice display constitutive nuclear accumulation of NRF2 and exhibit weaning-age lethality, due to orthohyperkeratosis of the esophagus and forestomach, resulting in malnutrition [ 3 ]. To date, there has been an increasing amount of evidence that underscores the indispensable functions of the KEAP1-NRF2 system in epidermal keratinization and various skin disorders [ 4 , 5 ]. These studies suggest that NRF2 plays a key role in skin homeostasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%